Viral Infection of Transgenic Mice Expressing a Viral Protein in Oligodendrocytes Leads to Chronic Central Nervous System Autoimmune Disease - Evans, Claire F. (The Rockefeller University Press, 1996)
One hypothesis for the etiology of central nervous system (CNS) autoimmune disease is that infection by a virus sharing antigenic epitopes with CNS antigens (molecular mimicry) elicits a virus-specific immune response that also recognizes self-epitopes. To address this hypothesis, transgenic mice were generated that express the nucleoprotein or glycoprotein of lymphocytic choriomeningitis virus (LCMV) as self in oligodendrocytes. Intraperitoneal infection with LCMV strain Armstrong led to infection of tissues in the periphery but not the CNS, and the virus was cleared within 7–14 d. After clearance, a chronic inflammation of the CNS resulted, accompanied by upregulation of CNS expression of MHC class I and II molecules. A second LCMV infection led to enhanced CNS pathology, characterized by loss of myelin and clinical motor dysfunction. Disease enhancement also occurred after a second infection with unrelated viruses that cross-activated LCMV-specific memory T cells. These findings indicate that chronic CNS autoimmune disease may be induced by infection with a virus sharing epitopes with a protein expressed in oligodendrocytes and this disease may be enhanced by a second infection with the same or an unrelated virus. These results may explain the association of several different viruses with some human autoimmune diseases.